Design, synthesis, and biochemical assay of peptide inhibitors derived from α-enolase for use against peptidylarginine deiminase type 4 - Ahmad Nadzirin, Izzuddin (2013)
Rheumatoid arthritis (RA) is an inflammatory autoimmune disease affecting about 0.5–1.0% of the world population. Peptidylarginine deiminase type 4 (PAD4) is a responsible protein for the occurrence of RA by catalyzing citrullination of proteins. The citrullinated proteins act as autoantigens by stimulating an immune response. Citrullinated α-enolase was identified as one of autoantigens for RA. Hence, α-enolase serves as a good template for design of potential peptide inhibitors against PAD4. The binding affinity of α-enolase-derived peptides and PAD4 was virtually determined using PatchDock and HADDOCK docking programs. Synthesis of the designed peptides was performed using a solid phase peptide synthesis (SPPS) method. The inhibitory potential of each peptide was determined experimentally by PAD4 inhibition assay and IC50 measurement. Based on the virtual experiment, binding energies given by molecular docking data suggested that N-P1 and NP-2 peptides were the most active substrates of PAD4. The synthesis of these peptides using SPPS yielded peptides with purity of more than 60%. PAD4 activity assay data showed that the N-P2 peptide was the most favourable substrate among all peptides. Further modification of N-P2 by changing the Arg residue to canavanine (P2 (Cav)) rendered it an inhibitor against PAD4 by reducing the PAD4 activity to 35% with IC50 1.39 ± 0.3 mM. The binding of P2 (Cav) and PAD4 changed the secondary structure of the peptide as indicated by circular dichroism spectroscopic data. As a conclusion, P2 (Cav) is a potential inhibitor against PAD4 and can serve as a starting point for the development of even more potent inhibitors.